Peradaban Islam di Nusantara dan Perkembangan Pendidikannya: Perspektif QS. At-Taubah Ayat 122 - Siti Auliaul Azizah; Nafisa Anggie Nilam Sari; Juwita Mayla Mustikasari (Universitas Negeri Gorontalo, 2026)
Islamic civilization in the Nusantara developed through a process of Islamization supported not only by da'wah activities but also by the growth of Islamic education as a medium for knowledge transmission and the formation of Muslim society. This study aims to analyze the development of Islamic civilization in the Nusantara and the evolution of its educational system from the perspective of Qur'an Surah At-Tawbah verse 122. This research employed a qualitative approach using a library research method. Data were collected from the Qur'an, tafsir literature, books, and relevant scientific articles, and were analyzed through content analysis and descriptive-critical analysis. The findings reveal that Islamic educational institutions, such as pesantren, surau, and dayah, have played a significant role in fostering intellectual traditions, strengthening Islamic identity, and sustaining the continuity of Islamic civilization in the Nusantara. The perspective of Surah At-Tawbah verse 122 emphasizes that the concept of tafaqquh fi al-din serves as the foundation of educational development, focusing not only on the deep understanding of knowledge but also on the social responsibility to guide society. These findings indicate that Islamic education constitutes a fundamental pillar in the formation and development of Islamic civilization in the Nusantara and remains relevant in addressing contemporary educational challenges.